PATHOMORPHОLOGY OF BILIARY ATRESIA IN CHILDREN – RECIPIENT OF LIVER - O. E. Iryshkin; I. M. Iljinsky; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2014)
Aim of the work. Сlinical and morphological research of the features of biliary atresia at children-recipients of liver, to whom a portoenterostomy was made in comparison with patients to whom such surgery wasn't carried out. Materials and methods. Clinical records and histological research of liver of 49 children suffering a bili- ary atresia are analyzed. Two groups were created: the 1st group – 21 children without portoenterostomy before liver transplantation and 2nd group – 28 children with portoenterostomy before liver transplantation. Results. Pathomorphology of liver the characteristics in structure of proliferation bile ducts are established: hypostasis and dystrophic changes of cholangiocytes at patients of the first group (p = 0,035) and sclerosis of bile ducts with disappearance of an epithelium at patients of the second group (p = 0,01). In first group of children activity of inflammatory process in liver were significantly higher than in second group (p = 0,02). Conclusion. Our experi- ence has demonstrated that portoenterostomy doesn’t prevent fibrosis of intrahepatic bile ducts and development of fibrosis, and then a development of cirrhosis.